Pengaruh Kualitas Pelayanan Terhadap Kepuasan Pelanggan Pada Galeri Indosat Solo - Marfuatun, Mira Isnaini; , Drs. Wiyadi, M.M., Ph.D (2017)
This research aim to know how influence of service quality covering factor of tangibles, reliability, responsiveness, empathy, and assurance to satisfaction of customer at Galeri Indosat Solo. Technique intake of sample the used is non probability sampling with method of accidental sampling. Population and sample of used at this research is customer of Galeri Indosat Solo amounting to counted 100 respondents. Hypothesis tested in this research use analyzer validity test, reliabilities test, classical assumption tests, doubled linear regression, F test, coefficient of determinacy (Adjusted R2), and t test. Result of the research indicate that the service quality in the dimension of tangibles, reliability, responsiveness, assurance, and empathy by together have an effect on positive to customer satisfaction. Result ofthe test coefficient of determinacy (adjusted R2) show customer satisfaction influenced by service quality in the dimension of tangibles, reliability, responsiveness, assurance, and empathy equal to 39%, and the model have got away from the tested ofclassic assumption. Keyword: service quality, tangibles, reliability, responsiveness, assurance, empathy, customer satisfaction.